Evaluation on the Performance of MICP Treated Slope Soil Under Acid Rain Environment. - Gowthaman, S.; Mohsenzadeh, A.; Nakashima, K.; Nakamura, H.; Kawasaki, S. (GEOMATE International Society., 2020)
Microbial induced carbonate precipitation (MICP), through the field of bio-mediated geotechnical engineering, has gained significant momentum in research industry during recent past, which has promoted the strategy nearly to field application stage. The aim of this study is to evaluate the durability of MICP specimens under the exposure of acidic environment. The representative soils from an erosion prone slope were treated to different cementation levels on the basis of MICP. The acidic environment was enabled under different pH conditions (ranging 3.0-6.0) through two different mechanisms: (i) infiltration and (ii) immersion, both of which represent acid rainfall and water-logged environments, respectively. The influence of infiltration rate was studied under two potential rainfall intensities, and in each case, specimens were infiltrated by acid rain volume equals fifteen-year rainfall volume. The results indicate that decrease in environment pH increased the corrosion of CaCO3, resulting considerable loss in both mass and unconfined compressive strength (UCS). However, the increased cementation level showed high durability of specimens. The results also revealed that the contact time of acid rain significantly governed the rate of corrosion, i.e. specimens subjected to lower infiltration rate showed higher loss of mass and UCS compared to that of higher rate. Moreover, the immerged specimens showed relatively a similar response of those subjected to low infiltration. Overall, this study addressed one of the prime environmental hurdles which might possibly be experienced in the field, advancing the understanding on performance of slope near-surfaces conserved by MICP.
Keywords: Microbial induced carbonate precipitation (MICP); Slope near-surface stabilization.; Durability; Acid rain; Cementation level